Foreign Policy in the Trump Era: Populist Rhetoric and the United States Membership in NATO - Laretna Pranadian Rahajeng (Global Local Interactions: Journal of International Relations, 2019)
This study aimed to analyze the impact of President Donald Trump's populist rhetoric on the United States foreign policy towards NATO. Issues regarding the United States membership in NATO surfaced through allegations made by Trump's presidential campaign that criticized and questioned the relevance of NATO for American interests. In the past, NATO was considered to be one of the most crucial alliances for the United States as its membership had constantly become an agenda for the United States foreign policy. Nonetheless, Trump's hostile attitude against NATO shown a significant departure from previous administrations. The results of this research have shown that the populist rhetoric was used as a powerful campaign strategy to gain votes in the presidential election. Specifically, this strategy exploited the public unrest among American people regarding the United States involvement in the international level. Additionally, the results also showed that the populist rhetoric was also used to advance the United States' interest to encouraged an institutional change within NATO in which other member countries must increase their contribution to the alliance.